Energy Requirement for Maintenance and Egg Production for Broiler Breeder Hens - Reyes, M.E.; Salas, C.; Coon , C.N. (International Journal of Poultry Science, 2011)
Mathematical modeling is an accounting tool that can be used for predicting the nutritional requirements for poultry with different genetic strains, environments and stages of meat gain or egg production. Models are also useful for describing or predicting the animal’s production process. Modeling the daily ME requirement of broiler breeder hens requires partitioning Metabolizable Energy (ME) requirements into maintenance, egg mass and body weight gain. Determining the daily energy requirement for maintenance and egg production in breeders requires separating the daily energy needs for egg production from energy needs of maintenance. The objective of the research reported herein was: 1.) to obtain information about body tissue changes and egg composition for breeders being fed specific intakes of ME in a set environment and 2.) to evaluate a technique for partitioning the Metabolizable Energy (ME) requirement into maintenance and production for each individual breeder. An estrogen antagonist, TAMOXIFEN ([Z]-1-1[p-Dimethylaminoethoxyphenyl]-1,2-diphenyhl-1butene) (TAM), was used to separate the ME needs into two periods: laying and non-laying. Broiler breeder hens were provided TAM to stop egg production and their individual ME requirement for maintenance determined. Each broiler breeder resumed egg production when TAM was withdrawn and the ME requirement for egg production and BW gain determined. The estimated ME required for maintenance for breeders (MEm) housed in a constant 21C was 98.3 kcal/kgBW0.75, MEg for gain was 5.6 kcal/g and MEe for egg mass was 2.4 kcal/g. The energy efficiencies for protein gain (kp), fat gain (kf) and egg calories (ke) were 34%, 79% and 65.7%, respectively. The use of TAM provided an opportunity to estimate breeder maintenance requirements and reduce the interdependence in estimating factorial coefficients while partitioning production energy.